(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper, we introduce the class ( , , , ) On a b g x by using the Ruscheweyh Operator. The aim of this paper is to study some properties of this class,like, coefficient inequality, Hadamard products, Extreme points, radius of starlikeness and convexity, closure theorem of a class of analytic and univalent function in the unit disc. The results obtained here are found to be sharp.